PERGESERAN MAKNA RELIGIUS: PENGARUH INTERAKSI BUDAYA GLOBAL TERHADAP TRADISI LOKAL - Aslan, Aslan; Melyana R Pugu (Prosiding Seminar Nasional Indonesia, 2025)
This study discusses the shift in religious meaning in local traditions as a result of increasingly intensive global cultural interaction in the era of globalisation. Using a literature review method, this study examines various forms of change that have occurred in the implementation and interpretation of religious traditions in society, and identifies the main driving factors, such as globalisation, modernisation, urbanisation, technological developments, and lifestyle changes. The findings reveal that local religious traditions are shifting from a sacred dimension towards a more secular and symbolic dimension, with a decline in community participation and the commodification of traditions. However, there are efforts to revitalise and adapt traditions to remain relevant amid the tide of change. This study emphasises the importance of preserving religious values through creative and collaborative approaches to maintain local cultural identity in the global era.